Edukasi Pencegahan Kekerasan Seksual Pada Remaja di SMK Bhakti Kencana Majalaya - Pratama, Reza; Amini, Nadia Ushfuri; Rahayu, Sri Mulyati; Isronijaya, Mohamad; Fitria, Elli; Hidayatullah, Anna Ikhsan (Kolaborasi Masyarakat, 2025)
The adolescent phase, which is a transition period between childhood and adulthood, creates its own challenges with physical, emotional and social changes. The influence of mass media, especially social media, can lead to negative impacts, including the risk of sexual violence. Using educational and interactive methods, the socialization process involves students from various fields of study to provide vocational students with an understanding of the types of sexual violence, how to avoid it, and positive behavior in social media. The evaluation results through pre and post-tests indicate an increase in students' knowledge after the socialization. A 92% of the students understand that sexual violence can happen to anyone, and 100% of the students comprehend the importance of proper internet etiquette and the risks associated with irresponsible use of social media. From the results, it is evident that this approach is effective in raising students' awareness about the risks of sexual violence and the importance of parents' role in the use of social media.